2018
DOI: 10.1016/j.yexcr.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The formation of giant plasma membrane vesicles enable new insights into the regulation of cholesterol efflux

Abstract: Aberrant cellular cholesterol accumulation contributes to the pathophysiology of many diseases including neurodegenerative disorders such as Niemann-Pick Type C (NPC) and Alzheimer's Disease. Many aspects of cholesterol efflux from cells remain elusive. Here we describe the utility of cholesterol-rich giant plasma membrane vesicles (GPMVs) as a means to monitor cholesterol that is translocated to the plasma membrane for secretion. We demonstrate that small molecules known to enhance lipid efflux, including tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…These GPMVs fill a unique niche, maintaining the approximate lipid and protein content of living membranes while offering the experimental tractability of synthetic models (3). This combination has allowed investigation of PM composition (4), physical properties (5-7), dynamics (8,9), and potentially signaling and transport (8,(10)(11)(12)(13) in isolation from the complexity of living cells.…”
Section: Introductionmentioning
confidence: 99%
“…These GPMVs fill a unique niche, maintaining the approximate lipid and protein content of living membranes while offering the experimental tractability of synthetic models (3). This combination has allowed investigation of PM composition (4), physical properties (5-7), dynamics (8,9), and potentially signaling and transport (8,(10)(11)(12)(13) in isolation from the complexity of living cells.…”
Section: Introductionmentioning
confidence: 99%
“…These GPMVs fill a unique niche, maintaining the approximate lipid and protein content of living membranes while offering the experimental tractability of synthetic models (3). This combination has allowed investigation of PM composition (4), physical properties (5)(6)(7), dynamics (8,9), and potentially signaling and transport (8,(10)(11)(12)(13) in isolation from the complexity of living cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on NPC1 mutant cells proposed that cyclodextrin induces the secretion of cholesterol in vitro (Chen et al, 2010;Feltes et al, 2020;Ilnytska et al, 2021;Juhl et al, 2021;Sedgwick et al, 2018;Vacca et al, 2019) probably by distinct modes depending on cell type and experimental conditions. Our observations on primary cultures suggested that CD .…”
Section: Discussionmentioning
confidence: 97%